2014
DOI: 10.1073/pnas.1311968111
|View full text |Cite
|
Sign up to set email alerts
|

C1q as a unique player in angiogenesis with therapeutic implication in wound healing

Abstract: We have previously shown that C1q is expressed on endothelial cells (ECs) of newly formed decidual tissue. Here we demonstrate that C1q is deposited in wound-healing skin in the absence of C4 and C3 and that C1q mRNA is locally expressed as revealed by real-time PCR and in situ hybridization. C1q was found to induce permeability of the EC monolayer, to stimulate EC proliferation and migration, and to promote tube formation and sprouting of new vessels in a rat aortic ring assay. Using a murine model of wound h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
120
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(140 citation statements)
references
References 28 publications
6
120
0
1
Order By: Relevance
“…Because angiogenesis plays a key role in wound healing and complement has been suggested to be involved in angiogenesis (9, 21), we stained wounded tissue sections with an antibody against α-SMA to assess vascularization. We detected significantly increased numbers of α-SMA + vessels in the hypodermis of C3 −/− mice compared to C3 +/+ mice (p=0.001) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because angiogenesis plays a key role in wound healing and complement has been suggested to be involved in angiogenesis (9, 21), we stained wounded tissue sections with an antibody against α-SMA to assess vascularization. We detected significantly increased numbers of α-SMA + vessels in the hypodermis of C3 −/− mice compared to C3 +/+ mice (p=0.001) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, C1q has been reported to play an important role in nerve pruning (Stevens et al, 2007) Wnt/Beta-catenin signalling (Naito et al, 2012;Sumida et al, 2015). Also a role for C1q was reported on neoangiogenesis (Bossi et al, 2014).…”
Section: C1q Traditional and Non-traditional Rolesmentioning
confidence: 99%
“…Recent studies have demonstrated its involvement in several physiological processes via binding with its specific receptors. 9 Among the processes induced by the non-classical functions of the C1q molecule, we find: the modulation of various immune cells, 10 the regulation of cell migration (chemotaxis), adhesion, survival and differentiation, 11 coagulation, 12 angiogenesis 13 and embryonic development, including neurological synapse function. 14 There is mounting evidence to support the idea that C1q and its receptors are also involved in the regulation of cancer.…”
Section: Introductionmentioning
confidence: 95%